Kritik Pemahaman Hadist Nabi Tentang Keutamaan Surat Al-Waqi'ah - Surahmat Surahmat (LPPM IAI Hasanuddin Pare-Kediri, 2015)
Hadith Studies urgent put forward, especially the problem of understanding. In this study, the authors focused on the understanding of hadith criticism about the virtues of a letter al-Waqi'ah. Fairly comprehensive study has been written by Muhammad Makhdlori, Read Surah Al-Waqi'ah Then you will be rich. It is set out on the phenomena found in the community, some of which assume that the letter of al-Waqiah practice can cause a person to become rich. Is it true that this argument? The method I use is the hadith criticism in the sense mengkomparasikan hadith al-Waqi'ah letter with a variety of texts, both the Qur'an, hadith setema, and logic. After takhrij, this hadith al-Isnad da'if quality, nevertheless after study of matannya, then substance acceptable Hadith (maqbul) with understanding who read the letter al-Waqi'ah surely he would not hit indigent (poverty heart ) as Prophet Muhammad: wealth (intrinsic) is not in the abundance of things which have, however, lies in the wealth of a person's soul or heart (qona'ah; willingly accept any gift, sometimes a lot, sometimes a little, because only God alone more determine the extent of the needs of every servant).